Determinants of primary school dropout in Nawalparasi District - Manandhar, N; Sthapit, AB (Journal of College of Medical Sciences-Nepal, 2012)
Nepal’s school education is structured as ECD / PPC, primary, lower secondary, secondary and higher secondary education. There are 29,220 primary schools. Any school children absent in the school for four consecutive weeks or more who failed to appear in final examination or next year in same school is considered as dropouts. To assess the causes of dropout in primary schools of Gaindakote Resource Centre of Nawalparasi district, a cross-sectional study was conducted in twelve schools of Gaindakote Resource Centre of Nawalparasi district during the period of Srawan / Bhadra, 2066 B.S. The highest dropout rate was found to be 8.43% in grade I and followed by 7.47%, 4.33%, 4.23% and 1.83% in grades II,III, IV andV respectively. The dropout rate for girls (5.87%) was less than boys (6.14%). Drop out is considered as huge waste of resources of the country as well as individual and it is a complex social problem. To reduce dropout rate in primary school, only free education will not solve the problem. So Government alone cannot solve it. Community must be made aware about the problems of drop out & parents are to be motivated for sending their children to school. Journal of College of Medical Sciences-Nepal,2011,Vol-6,No-4, 14-18 DOI: http://dx.doi.org/10.3126/jcmsn.v6i4.6720